Anchoring Zn0.5Cd0.5S solid solution onto 2D porous Co–CoO nanosheets for highly improved photocatalytic H2 generation. (27th August 2021) - Gao, Xueyou; Zeng, Deqian; Zeng, Qingru; Xie, Zongzhuo; Fujita, Toyohisa; Wang, Xinpeng; He, Gang; Wei, Yuezhou
Abstract : Two-dimensional porous Co–CoO nanosheets act as an efficient cocatalyst to reduce the HER overpotential and boost the charge separation of Zn0.5 Cd0.5 S nanocrystals. Abstract : Co-Based cocatalysts have attracted considerable attention as potential alternatives for the noble metal (Pt) in photocatalytic water splitting. However, the two-dimensional (2D) porous-structured Co-based cocatalysts toward photocatalytic hydrogen (H2 ) production application are rarely reported. In this study, 2D porous Co–CoO (CC) nanosheets prepared by a facile annealing approach were employed as a support to anchor Zn0.5 Cd0.5 S (ZCS) solid solution toward visible-light-induced photocatalytic H2 production. The optimized 5CC/ZCS composite exhibits a high H2 generation rate of 8152 μmol h −1 g −1, which is approximately 46- and 10-fold that of pristine ZCS and 3% Pt/ZCS, respectively. Moreover, the Co–CoO/Zn0.5 Cd0.5 S (CC/ZCS) also processes long-term activity and superior stability during the photocatalytic H2 -evolution reactions. The significant improvement in the photocatalytic water splitting of CC/ZCS is mainly derived from the intimate interface between CC nanosheets and ZCS nanoparticles. The 2D porous CC nanosheets serve as an efficient cocatalyst to promote photogenerated charge carrier separation, reduce reaction overpotential, and provide abundant reaction sites. This work paves a promising way to construct hybrid nanostructures based on porous Co-based nanosheets and metal sulfides for enhanced photo/electro-catalysis.